'Ad Maiorem Poloniae Gloriam!' Polish Inter-colonial Encounters in Africa in the Interwar Period. Issue 5 (2nd September 2020) - Grzechnik, Marta
ABSTRACT: This paper discusses the Polish Maritime and Colonial League's ambitions to acquire colonies in Africa for Poland in the interwar period, using two cases of expeditions to Africa organised by the League: 1928 expedition to Angola and M/S Poznań 's 1935 trade expedition to West Africa. These cases serve as examples of newcomers in the race for colonies who attempted to carve their share in Africa's resources by cooperation with Africans and European colonial powers, and the ways in which knowledge production and knowledge retrieval were used in the process. They reproduced European stereotypes about Africa and Africans, conceptualised Africa as terra nullius waiting to be cultivated by Europeans, and themselves as white Europeans destined to do this. Despite lack of lasting success of the League's projects, they reveal a network of colonial and inter-colonial encounters in Africa encompassing the existing empires and Africans, but also aspiring colonials. Thus, rather than a marginal phenomenon, they appear as one having a global context, entangled in the circulation of ideas and peoples, networks of competition and cooperation across and beyond colonial empires.